Animal Ownership Among Vulnerable Populations in Regional South Australia: Implications for Natural Disaster Preparedness and Resilience. Issue 1 (January 2017) - Thompson, Kirrilly; Trigg, Joshua; Smith, Bradley
Abstract : Context: Few studies have examined the prevalence of animal ownership among populations likely to be at greater risk from disaster events within a bushfire context. Objective: To investigate the proportion of vulnerable community members keeping animals and the types of animals kept, as well as perceived risk of harm to pets, and their inclusion in bushfire survival planning. Design: Statewide anonymous online survey in 2014 of adult South Australian animal owners threatened by bushfire in January 2014. Respondents were asked about animal ownership, their bushfire risk perception, and household survival planning. Descriptive statistics are presented for 5 groups considered likely to contribute to increased risk of harm for households: linguistically diverse, older adults, families with young children, physically frail, and self-identifying disabled, as well as individuals with mental health considerations. Setting: An opt-in purposively targeted sample of anonymous South Australians living in high fire-risk locations. Participants: Adult South Australian animal owners threatened or directly impacted by bushfire events, including individuals matching 1 of the 5 vulnerable groups. Main Outcome Measures: Self-reported details of animal ownership, perceived fire risk, survival planning, and vulnerability characteristics. Results: Animal ownership was found to be more prevalent in these 5 populations than in the wider South Australian population. Perceived risk to pets was low to moderately low in these individuals. Variation was observed in the role of animals generally and pets specifically as motivators for preparing bushfire survival plans. Conclusions: Emergency services and associated agencies need to consider how the unique needs of vulnerable populations that keep animals, and their potential differences in risk perception, relate to their bushfire survival planning and preparedness requirements.